PENGARUH PEMAHAMAN WAJIB PAJAK DAN MANFAAT PAJAK RESTORAN TERHADAP KESADARAN WAJIB PAJAK MEMBAYAR PAJAK (STUDI KASUS PADA USAHA RESTORAN DI KOTA TOMOHON) - Butarbutar, Arian Sumando; Sabijono, Harijanto; Wokas, Heince R.N (GOING CONCERN : JURNAL RISET AKUNTANSI, 2014)
This study aims to determine the effect of taxpayer understanding and awareness of tax benefits to the restaurants taxpayer pays taxes . Sources of data used in this study is primary data derived from taxpayer restaurant in Tomohon. The analytical method used is multiple regression analysis. The results of the regression analysis resulted in the equation r Y = 8.000 + 0.136 X1 + 0.440 X2 . R2 value of 0.303 indicates the proportion of the taxpayer contributes understanding and awareness of tax benefits to the restaurants taxpayer pays tax at a restaurant in Tomohon 30.3 %. And korelsi coefficient ( r) of 0.550 . Hypothesis testing using t-test showed that no taxpayer understanding partial effect on consciousness taxpayer pays tax while the restaurant in Tomohon city restaurant tax benefits significantly influence the consciousness of the top tax payers in the city of Tomohon.